Framing the Coverage of the Lebanon Conflict: An Entman Framing Analysis of AP News, Reuters, and The Guardian’s Reporting on Israeli Attacks on Beirut - Nazifatul Mardiah; Anwar Masadi (Journal of Pragmatics Research, 2026)
Reporting on Israeli attacks on Beirut reveals divergent media framings of the Israel–Hezbollah conflict, demonstrating that media actively shape public perceptions rather than merely transmitting information. This study compares the framing of Israeli attacks on Beirut in AP News, Reuters, and The Guardian using Robert Entman’s framing analysis, focusing on problem definition, causal interpretation, moral evaluation, and treatment recommendation. Employing a descriptive qualitative method, thematically similar news articles published within comparable timeframes are analyzed to identify framing differences across outlets. The findings show that AP News adopts a security-oriented framing that presents Hezbollah as the main threat and legitimizes Israeli military actions, while Reuters offers a more balanced perspective by situating the attacks within concerns over escalation and regional stability. Conversely, The Guardian emphasizes humanitarian impacts, civilian casualties, and the escalation of violence. These differences indicate that media framing shapes the positioning of conflict actors, the construction of military legitimacy, and implied resolutions, confirming the media’s role as discursive actors in international conflict narratives.